Manejo adecuado de la historia clínica gineco obstétrica en mujeres embarazadas - Tenesaca Gonzalez, Maribel Estefania (Machala : Universidad Técnica de Machala, 2023)
ABSTRACT: Introduction: The clinical history can be established from various expressions and specific points, since there is a legal field, medical field, and/or legal medical field. In the case of obstetrics and gynecology, obtaining said information is also important in the reproductive field and promotion of healthy lifestyle habits. Objective: To analyze the importance of the gynecological-obstetric clinical history through the application of the state-of-the-art methodology to approach a correct diagnosis. Material and methods: The following descriptive bibliographic review is carried out with the search for scientific articles in the pages of Pubmed, Redalyc, Elsevier, Google Scholar, of the last 5 years to obtain an update on a scientific basis. Development: Carrying out a medical history allows us to know the chronic conditions of importance and other pathological antecedents that have not been treated but that had an impact on the patient's health. It is mentioned that performing light intensity physical exercise during pregnancy improves muscle tone, and even reduces the risk of preeclampsia, gestational diabetes, and postpartum overweight. Conclusions: The clinical history is a fundamental instrument in the management of the gynecological and obstetric patient. The same that must be systematic and complete, since it allows to know the risk factors of the woman, which could be complicated, which will make the gestational state take a high risk level.
RESUMEN: Introducción: La historia clínica se puede establecer desde varias expresiones y puntos específicos, pues existe un campo jurídico, campo médico, y/o campo médico legal. En el caso de la obstetricia y ginecología, la obtención de dicha información también es importante en el ámbito reproductivo y promoción de hábitos de vida saludables. Objetivo: Analizar la importancia de la historia clínica gineco-obstétrica mediante la aplicación de la metodología del estado del arte para el abordaje de un correcto diagnóstico. Material y métodos: Se realiza la siguiente revisión bibliográfica de tipo descriptivo con la búsqueda de artículos científicos en las páginas de Pubmed, Redalyc, Elsevier, Google Académico, de los últimos 5 años para obtener actualización de base científica. Desarrollo: La realización de un historial médico permite conocer los padecimientos crónicos de importancia y otros antecedentes patológicos que no hayan sido tratados pero que tuvieron un impacto en la salud del paciente. Se menciona que realizar ejercicio físico de leve intensidad durante el embarazo mejora el tono muscular, e incluso reduce el riesgo de preeclampsia, diabetes gestacional y sobrepeso en el puerperio. Conclusiones: La historia clínica es un instrumento fundamental en el manejo de la paciente ginecológica y obstétrica. La misma que debe ser sistemática y completa, puesto que permite conocer los factores de riesgo de la mujer, el cual podría complicarse lo que hará que el estado gestacional tome un nivel de riesgo alto.
Keywords: HISTORIA CLINICA; GINECO OBSTETRICA; MEDICO LEGAL; EMBARAZADAS